Efficiency & Profitability of Islamic Banking in Pakistan - Hina Hafiz; Dr. Zubair Arshad; Dr. Neelam Bano; Laiba Manzoor (Indus Journal of Social Sciences, 2025)
This research aims to compare the efficiency and profitability of Islamic Banks (IBs) and Islamic branches of Conventional banks (IBBs) for the period of 2015-2024 by using a non-parametric linear program Data Envelopment Analysis (DEA) in Pakistan. Technical Efficiency, Pure Technical Efficiency and Scale efficiency is measured to find out the performance and trends of physical resources, managerial skills and size of DMUs (Decision making units). Inputs (Total assets, Number of employees and operating cost) and outputs (net profit, deposits and ROE) are developed on the basis of intermediation-Cost Revenue approaches. The finding of this study shows that Full-fledged Islamic banks (IBs) are performing better in term of efficiency and profitability due to institutional autonomy, Strategic management orientation and scale efficiency. It also emphasizes the need to provide the Islamic windows/branches with strategic and operational independence to serve as similar to Islamic Banks in Pakistan.